Mentoring-Based Coaching to Form Innovative and Independent Student Entrepreneurship: Pembinaan Berbasis Pendampingan untuk Membentuk Kewirausahaan Mahasiswa yang Inovatif dan Mandiri - Denny Astrie Anggraini; Sri Fitria Retnawaty; Wan Laura Hardilawati; Yeeri Badrun; Retno Tri Wahyuni (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Universitas Muhammadiyah Riau (UMRI), one of the campuses that supports development programs, has carried out planning and coaching students to become entrepreneurs. This can be seen from the level of participation and success of UMRI students in several student competitions, such as PKM-Entrepreneurship, P2MW, and Entrepreneurship Award. However, after the competition, many student businesses closed due to inadequate business management, equipment, and other factors. Therefore, this coaching program was carried out. The methods used are socialization, selection, provision, increasing tenant capacity (entrepreneurship training and internships), providing science and technology as well as business capital, mentoring, and evaluation monitoring. As a result of this activity, there are 20 student tenants who partner with 10 types of products. There has been an increase in tenant capacity with training, onboarding (internships), mentoring, and application of science and technology, as well as capital provided. It is hoped that this increase in tenant capacity will also improve their business skills so that their business can run well.